2009
DOI: 10.1016/j.freeradbiomed.2009.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts from long-lived mutant mice show diminished ERK1/2 phosphorylation but exaggerated induction of immediate early genes

Abstract: Skin-derived fibroblasts from long-lived mutant mice, including the Snell dwarf mice and mice defective in growth hormone receptor ("GHRKO"), are resistant to death induced by oxidative stresses or by UV light, but the molecular mechanism for their stress resistance is unknown. The present study showed that phosphorylation of the stress-activated protein kinases ERK1/2 induced by peroxide, cadmium, or paraquat was attenuated in cells from these mice. Induction of ERK phosphorylation by UV light was not altered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 41 publications
2
29
0
Order By: Relevance
“…Levels of these IEGs rise very rapidly in response to various forms of stress (24), and activation of PI3K-Akt and MAPK signaling pathways is involved in these responses (25,26). Our studies of Snell dwarf fibroblasts in culture (18) have shown, surprisingly, that dwarf cells showed stronger induction of ERK-dependent IEG mRNAs despite the relatively low levels of p-ERK induction. In these earlier studies, we also found that IEG activation was blocked in control and dwarf cells by MEK inhibition, showing that ERK phosphorylation is required for IEG activation.…”
Section: Stress-induced Expression Of Immediate Early Gene (Ieg) Famimentioning
confidence: 67%
See 3 more Smart Citations
“…Levels of these IEGs rise very rapidly in response to various forms of stress (24), and activation of PI3K-Akt and MAPK signaling pathways is involved in these responses (25,26). Our studies of Snell dwarf fibroblasts in culture (18) have shown, surprisingly, that dwarf cells showed stronger induction of ERK-dependent IEG mRNAs despite the relatively low levels of p-ERK induction. In these earlier studies, we also found that IEG activation was blocked in control and dwarf cells by MEK inhibition, showing that ERK phosphorylation is required for IEG activation.…”
Section: Stress-induced Expression Of Immediate Early Gene (Ieg) Famimentioning
confidence: 67%
“…The level of ERK phosphorylation induced by these stresses is, however, significantly lower in cells from Snell dwarf mice, suggesting defects in the pathways that sense cellular injury and lead to activation of the kinase MEK, responsible for phosphorylation of ERK (18). Paradoxically, despite the relatively low induction of ERK phosphorylation, cells from Snell dwarf mice show abnormally high levels of mRNA accumulation for a series of ERK-sensitive genes, including Egr-1, Fos, and Jun (18). Moreover, recently p38 phosphorylation was reported to occur in fibroblasts from Ames mice in response to the mitochondrial inhibitor rotenone, and cells from dwarf mice had an attenuated response compared with control cells (19).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, we hypothesized that fibroblasts from longlived birds would also be more resistant to stress than cells from short-lived birds. In the case of mice, cells from long-lived stocks differ from control cells in DNA repair capacity (Salmon et al, 2008b), and signaling through the Nrf2 (Leiser and Miller, 2009) and MAP kinase pathways (Sun et al, 2009), although the extent to which these differences affect cells in vivo is unclear, as is whether differential signaling through these pathways is conserved among long-lived species.…”
Section: Introductionmentioning
confidence: 99%